Transfigured not Conformed: Christian Ethics in a Hermeneutic Key - Ulrich, Hans G.; Brock, Brian (Bloomsbury Publishing Plc., 2021)
The moral theology of Hans G. Ulrich is presented here in English for the first time. These collected essays represent the culmination of a lifetime of reflection on Christian living from this German theologian in conversation with Luther, Bonhoeffer, and contemporary philosophers and theologians. Ulrich's ethics affirm the lively presence of the living work of God in orienting the daily life of Christians. This presence enables members of the Church to live as creatures trusting in God's promises, bearing witness in political and economic spheres, and trusting in life as a gift in response to bioethical issues. Ulrich's fresh take on living out of the promise of God yields further guidance on issues in international relations, economics, parenting, disability, and more.
CRIS-Team Scopus Importer:2024-12-16